2020
DOI: 10.1080/00365521.2020.1807597
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for endoscopic submucosal dissection of early colorectal neoplasms with a monopolar scissor-type knife: use of the cumulative sum method

Abstract: Objective: Although scissor-type knives such as the Stag-Beetle (SB) Knife Jr are expected to result in a safe and easy colorectal endoscopic submucosal dissection (CR-ESD), information regarding the learning curve is lacking. Therefore, this study evaluated the learning curve with using SB Knife Jr. Materials and methods: We retrospectively reviewed 507 CR-ESD procedures performed in 464 patients using SB Knife Jr. The primary endpoint was a learning curve to achieve a satisfactory complete resection rate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The potential of ESD resection is limited by the difficulty in conducting the procedure as the length of procedure for ESD even when performed by experienced endoscopists can be three times longer than that for EMR[ 43 ]. However, the advancement in endoscopic resection equipment has been shown to shorten the procedure time despite a relatively short training duration[ 44 ]. Using the cumulative sum method, Miyakawa et al [ 44 ] recently reported the use of Stag-Beetle Knife Jr for ESD in a Japan single-center study generated good learning curve to achieve satisfactory resection speed (min/cm 2 ), which allowed the acquisition of proficient and safe skills within 120 cases[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of ESD resection is limited by the difficulty in conducting the procedure as the length of procedure for ESD even when performed by experienced endoscopists can be three times longer than that for EMR[ 43 ]. However, the advancement in endoscopic resection equipment has been shown to shorten the procedure time despite a relatively short training duration[ 44 ]. Using the cumulative sum method, Miyakawa et al [ 44 ] recently reported the use of Stag-Beetle Knife Jr for ESD in a Japan single-center study generated good learning curve to achieve satisfactory resection speed (min/cm 2 ), which allowed the acquisition of proficient and safe skills within 120 cases[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the advancement in endoscopic resection equipment has been shown to shorten the procedure time despite a relatively short training duration[ 44 ]. Using the cumulative sum method, Miyakawa et al [ 44 ] recently reported the use of Stag-Beetle Knife Jr for ESD in a Japan single-center study generated good learning curve to achieve satisfactory resection speed (min/cm 2 ), which allowed the acquisition of proficient and safe skills within 120 cases[ 44 ]. Other alternatives to ESD do exist, such as hybrid ESD and pre-cut EMR.…”
Section: Discussionmentioning
confidence: 99%
“…Although the previous reports suggested that tumor size, location, and use of antiplatelet agents are the risk factors of delayed bleeding, these were not relevant [37][38][39][40]. This study validated CR-ESD using scissor-type knives such as SB Knife Jr. SB Knife Jr also has a function as hemostatic forceps and enables hemostasis or precoagulation without device replacement and may lead to low delayed bleeding rate as compared with the conventional needle-type knife [41,42]. These facts might be the reason for the small number of delayed bleeding cases, which did not result in significant differences in risk factors.…”
Section: Discussionmentioning
confidence: 77%
“…44 However, the advancement in endoscopic resection equipment has been shown to shorten the procedure time despite a relatively short training duration. 45 Using the cumulative sum (CUSUM) method, Miyakawa et al recently reported the use of Stag-Beetle Knife Jr for ESD in a Japan single-center study generated good learning curve to achieve satisfactory resection speed (min/cm 2 ), which allowed the acquisition of pro cient and safe skills within 120 cases. 45 Other alternatives to ESD do exist, such as hybrid ESD and pre-cut EMR.…”
Section: Discussionmentioning
confidence: 99%
“…45 Using the cumulative sum (CUSUM) method, Miyakawa et al recently reported the use of Stag-Beetle Knife Jr for ESD in a Japan single-center study generated good learning curve to achieve satisfactory resection speed (min/cm 2 ), which allowed the acquisition of pro cient and safe skills within 120 cases. 45 Other alternatives to ESD do exist, such as hybrid ESD and pre-cut EMR. This hybrid approach has been shown to have lower en bloc resection rate (68.4% vs 91.0%) and complete resection rate (60.6% vs 82.9%) than conventional ESD.…”
Section: Discussionmentioning
confidence: 99%